CONNECTION BETWEEN SOME MOTORIC ABILITIES WITH SUCCESS IN REALIZATION OF PROGRAMMED CONTENTS FROM THE AREA OF GYMNASTICS OF THE FOURTH GRADE OF HIGH SCHOOL - Jovica Petković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
This research is undertaken for the purpose of defi ning and determinating of the le vel of connection between some motoric abilities with effi ciency in realization of some pro gramme issnes in the area of gymnastic (stretched - legged jump and folded - legged jump). On the sample of fi fty students from the fourth grade of High school, examined stu dents have been tested on ten motoric tests and on two specifi c motoric assignmentsstre tched - legged jump and folded - legged jump. The results of this research clearly point that there exist the multitude of statistically important coeffi cients of correlation between treated motoric abilities and applied assignments